Use of Rapamycin in a Patient With Juvenile Myelomonocytic Leukemia: A Case Report - Shivani Y. Upadhyay MD; Satiro N. De Oliveira MD; Theodore B. Moore MD (SAGE Publishing, 2017)
The relapse rate for children with juvenile myelomonocytic leukemia (JMML) status post hematopoietic stem cell transplantation (HSCT) approaches 50% within 5 years. Graft-versus-leukemia (GVL) is thought to play important role in the treatment of JMML. For this reason, careful management of immunosuppressive drugs after HSCT is crucial. This case report demonstrates that rapamycin and GVL represent a viable medical strategy for the management of pediatric patients with JMML who relapse following status post-HSCT.